Rokan Hilir Riau Regional Government Policy in Managing Forest and Land Fires Fiqih Siyasah Perspective - Br Srg, Siti Khairani; Mukhsin, Abd. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Forest and land fires are a problem that continues to exist in Indonesia, especially in Rokan Hilir Regency, Riau. The local government of Rokan Hilir Regency has formed a regulation in 2017, in which the regulation includes the Masyarakat Siaga Bencana (DPC) which is expected to be an important instrument in dealing with fire disasters. This journal research is formulated on 3 (three) main problems, namely: 1). How are the efforts of the local government of Rokan Hilir Regency, Riau in dealing with forest and land fires by forming the Masyarakat Siaga Bencana (DPC)? 2). What is the impact of the local government policy of Rokan Hilir Regency, Riau in dealing with forest and land fires by forming the Masyarakat Siaga Bencana (DPC)? 3). How is the analysis of Fiqh Siyasah on the policy of the local government of Rokan Hilir Regency, Riau in dealing with forest and land fires by forming the Masyarakat Siaga Bencana (DPC)? Research results show that efforts of the Regional Government of Rokan Hilir Regency, Riau, in overcoming forest and land fires have been insensitively carried out, including by forming a Regional Regulation in 2017, which includes elements involving the community. The impact of the Regional Government Policy of Rokan Hilir Regency, Riau, in overcoming forest and land fires is only minimal. The community expects strict regulations and the attention of the regional government to provide incentives, training, and skills to the community. Fiqh Siyasah analysis of the policy of the Regional Government of Rokan Hilir Regency, Riau, in overcoming forest and land fires, is part of the government policy that must be obeyed by the community, as a form of obedience to the government as contained in the verse of the Al-Qur'an, chapter An-Nisa' / 4:59.